The effects of training interventions on modifiable hamstring strain injury risk factors in healthy soccer players: a systematic review - Schneider, C; Van Hooren, B.; Cronin, J.; Jukic, I. (Strength and Conditioning Journal, 2023)
Despite promising research on various soccer-specific injury prevention programs, hamstring strain injuries (HSIs) persist in being a major problem in the sport. Therefore, in an attempt to expand the current knowledge on the prevention of HSIs, this systematic review aimed to identify how modifiable risk factors for HSIs (hamstring strength, hamstring:quadriceps [H:Q] strength ratios, biceps femoris long head fascicle length, and hamstring angle of peak torque) were altered following various training interventions. The protocol was preregistered on PROSPERO (CRD42020177363). The literature search was conducted on PubMed, SportDISCUS, and Web of Science. Following the search process, 20 studies were included in the systematic review, and the methodological quality of these studies was reported. Interventions were categorized based on exercise characteristics (movement velocity and contraction type), and the effects of each intervention subgroup were analyzed separately for all proposed risk factors for HSIs. Our findings show that a broad variety of exercise types (i.e., high- and low-velocity movements, eccentric only and traditional exercises) improves all risk factors for HSIs compared with fewer exercise types. Therefore, these findings suggest that hamstring injury risk factors can best be modified using a wide variety of exercises compared with, for example, only 1 or 2 specific exercises.